Flat, Ferrocenyl‐Conjugated Peptides: A Combined Electrochemical and Spectroscopic Study. Issue 14 (20th July 2021) - Biondi, Barbara; Cardena, Roberta; Bisello, Annalisa; Schiesari, Renato; Cerveson, Laura; Facci, Martino; Rancan, Marzio; Formaggio, Fernando; Santi, Saverio
Abstract: We synthesized two homo‐peptide series, based on the C α, β ‐didehydroalanine residue. One series was functionalized with a ferrocene (Fc) moiety at the N‐terminus, the other series with a Fc at the C‐terminus. These conjugates adopt the flat, fully extended conformation, also known as 2.05 ‐helix. Cyclic voltammetry measurements revealed that the peptide length does not affect the redox behavior of Fc, independently on the peptide end at which it is appended. This outcome perfectly fits with the presence of fully‐extended peptides, as in this 3D‐structure the dipole moment is negligible. Thus, we confirm the results of our previous study with two Fc pendants: fully‐extended, α‐peptide stretches prevent or reduce the charge transfer along the peptide chain. Abstract : Peptide length does not matter : Despite their flat and fully‐extended conformation, C α, β ‐didehydroalanine (ΔAla) α‐peptide stretches prevent or reduce the charge transfer along the chain, as demonstrated by a joint electrochemical and spectroscopic study exploiting the alternative presence of one ferrocene at the N‐ or at the C‐terminus. Since the macrodipole moment is absent due to the orientation of the carbonyl groups, the peptide length has no influence on the redox behaviour of ferrocene.